Foreign Direct Investment in Producer Services: Theory and Empirical Evidence - Horst Raff; Marc von der Ruhr (Center for Economic Studies and ifo Institute (CESifo), 2001)
This paper examines the pattern of foreign direct investment (FDI) in producer services. We develop a model of FDI in these services and test its predictions using panel data on U.S.FDI in 25 host countries from 1976 to 1995. We find evidence that, in addition to governmental and cultural barriers, producer-service firms may face informational barriers to entry into foreign markets. The presence of such barriers provides a possible explanation for the observation that producer-service FDI tends to follow FDI by downstream industries.
Keywords: F23; 330